2009
DOI: 10.1002/jnr.22030
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐propionic acid attenuates neuronal damage and oxidative stress in the ischemic hippocampus

Abstract: Tryptophan-derived indole compounds have been widely investigated as antioxidants and as free-radical scavengers. Indole-3-propionic acid (IPA), one of these compounds, is a deamination product of tryptophan. In the present study, we used Mongolian gerbils to investigate IPA's neuroprotective effects against ischemic damage and its antioxidative effects in the hippocampal CA1 region (CA1) after 5 min of transient forebrain ischemia. The repeated oral administration of IPA (10 mg/kg) for 15 days before ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 55 publications
(60 reference statements)
2
104
1
Order By: Relevance
“…IPA has been shown to be a powerful antioxidant [71] and has been considered as a possible treatment for Alzheimer's disease [72] due to its ability to protect neurons and neuroblastoma cells against oxidative damage and death [73,74].…”
Section: Indole-3-propionic Acidmentioning
confidence: 99%
“…IPA has been shown to be a powerful antioxidant [71] and has been considered as a possible treatment for Alzheimer's disease [72] due to its ability to protect neurons and neuroblastoma cells against oxidative damage and death [73,74].…”
Section: Indole-3-propionic Acidmentioning
confidence: 99%
“…Thereafter, paraffin-embedded tissues were coronally sectioned on a microtome (Leica, Wetzlar, Germany) into 3-lm thickness containing the SSC or hippocampus, and they were mounted onto saline-coated slides. The sections were stained with cresyl violet acetate according to a previously described procedure (Hwang et al 2009). …”
Section: Experimental Animalsmentioning
confidence: 99%
“…The hippocampus, a part of limbic system in the brain, is involved in memory formation and affective state. In addition, this region is associated with some brain diseases such as seizure, ischemia, and Alzheimer's disease (Hwang et al 2009;Liu et al 2009). Recently, this region has received additional attention because neurogenesis occurs in the hippocampal dentate gyrus throughout life (Eriksson et al 1998;Gage et al 1998;McDonald and Wojtowicz 2005).…”
Section: Introductionmentioning
confidence: 98%
“…In this study, we observed, like other researches that significant neuronal loss occurred in the gerbil hippocampal CA1 region after 5 min of transient cerebral ischemia (Kirino and Sano 1984;Hwang et al 2009). We previously reported that NeuN-immunoreactive neurons were significantly decreased in the gerbil GL induced by transient cerebral ischemia (Hwang et al 2004).…”
Section: Discussionmentioning
confidence: 51%
“…Restoration of blood flow (reperfusion) was observed directly under the ophthalmoscope. The body (rectal) temperature under free-regulating or normothermic (37 ± 0.5°C) conditions was maintained with a rectal temperature probe (TR-100; YSI, USA) and thermometric blanket before, during and after the surgery until the animals fully recovered from anesthesia (Hwang et al 2009). Thereafter, animals were kept on thermal incubator (Mirae Medical Industry, South Korea) to maintain the body temperature of animals until the animals were killed.…”
Section: Induction Of Transient Ischemiamentioning
confidence: 99%